Latent class analysis of drinking game consequences among college drinkers. (March 2022) - Hoyer, Dennis; Correia, Christopher J.
Highlights: Latent class analysis identified three classes of drinking game participants. Classes differed in rates of endorsing specific types of negative consequences. Classes differed in drinking motives, impulsivity, and drinking game behaviors. Abstract: Participation in drinking games has been identified as one specific alcohol-related context linked to increased risk for heavier alcohol consumption and negative consequences among college students. Despite advances in drinking game research, questions remain about the different types of individuals at risk from participating. The current study utilized latent class analysis to classify individuals based on their endorsement of eight negative drinking game consequences from the Hazardous Drinking Games Measure. Analyses included identification of classes among 656 college students, followed by covariate analyses regressing class membership on motives for playing drinking games, general drinking motives, impulsivity facets, general problematic alcohol use, and specific drinking game behaviors. A total of three classes were identified, including a class with the fewest number of problems, a class with higher rates of hangovers and becoming sick, and a class with relatively higher rates of a majority of the other consequences. Classes differed in endorsement of motives, impulsivity facets, general problematic consumption, and drinking game behaviors. Generally, coping, conformity, and social general drinking motives; conformity and enhancement and thrills motives for playing drinking games; the impulsivity facet of negative urgency; the number of drinks consumed while playing drinking games; playing consumption type drinking games; and general problematic alcohol use were associated with more problematic class membership. Results highlight distinct classes of individuals at risk from drinking game participation. Recommendations for future studies and potential prevention and intervention efforts are also discussed.